Who's Getting Shots First? Dealing With the Ethical Responsibility for Prioritizing Population Groups in Vaccination. (July 2021) - Rogozea, Liliana M.; Sechel, Gabriela; Bularca, Maria C.; Coman, Claudiu; Cocuz, Maria E.
Abstract : Background: The current pandemic has raised several ethical dilemmas, related to conducting real-time trials for new treatments or vaccines or with decisions such as accessibility to vaccines. Study Question: Should there be a prioritization of access to the vaccine based on ethical and objective criteria or should the access be done at random? Study Design: To determine the ethics and reality of rationing the accessibility to anti-COVID vaccine according to the official strategies. Data Sources: The study is based on the consultation of (1) scientific articles from international databases (Google Scholar, PubMed, ProQuest, and Clarivate), (2) public health documents, and (3) official information of various governments. Results: The analyzed documents revealed that a few similarities can be observed in European countries when it comes to the first categories of people who have received the vaccine: people living in care facilities and medical staff; it can also be seen that the vaccination plan was adopted by each country for the needs and characteristics of its population, the prioritization being done in 2–14 stages; some of them divided, in their turn, into subsequent substages. Most of the states subject to the analysis assigned the medical staff in the first stage, followed by those in the sectors ensuring the maintenance of essential services, afterward by the elderly or people with comorbidities, only later to expand to other social categories. Conclusions: Prioritization of vaccine administration is not only necessary, unavoidable, but also problematic both ethically and logistically, which should involve leaders in the field of public health, but also medical staff, regardless of their specialization. Prioritization of vaccination can not only have an impact on individual health (physical and emotional) but also on society from public health, economic, and sociocultural point of view.